Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1101/cshperspect.a019695
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism in Fungal Pathogenesis

Abstract: Fungal pathogens must assimilate local nutrients to establish an infection in their mammalian host. We focus on carbon, nitrogen, and micronutrient assimilation mechanisms, discussing how these influence host -fungus interactions during infection. We highlight several emerging trends based on the available data. First, the perturbation of carbon, nitrogen, or micronutrient assimilation attenuates fungal pathogenicity. Second, the contrasting evolutionary pressures exerted on facultative versus obligatory patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 188 publications
(272 reference statements)
4
85
0
Order By: Relevance
“…In the bloodstream, readily fermentable sugars are present at 0.1-0.2%, and in other niches they are present at lower concentrations or completely absent (Brown et al, 2014; Lorenz et al, 2004; Ramirez and Lorenz, 2007). To infect humans, therefore, Candida must rely on utilization of suboptimal carbon sources, including lactate, acetate, fatty acids and amino acids (Ene et al, 2014). Might Inz-5 restrict the metabolic flexibility of C. albicans by preventing utilization of these carbon sources?…”
Section: Resultsmentioning
confidence: 99%
“…In the bloodstream, readily fermentable sugars are present at 0.1-0.2%, and in other niches they are present at lower concentrations or completely absent (Brown et al, 2014; Lorenz et al, 2004; Ramirez and Lorenz, 2007). To infect humans, therefore, Candida must rely on utilization of suboptimal carbon sources, including lactate, acetate, fatty acids and amino acids (Ene et al, 2014). Might Inz-5 restrict the metabolic flexibility of C. albicans by preventing utilization of these carbon sources?…”
Section: Resultsmentioning
confidence: 99%
“…Acquisition and utilization of available nutrients from the host is fundamental to the survival and pathogenicity of microorganisms, and the host uses nutrient deprivation and sequestration as a defense mechanism to limit microbial growth. Pathogens have to identify ready sources of nutrients in a host, and it is clear that some are scarce, such as nucleotides and iron, since mutants impaired in the synthesis or uptake of these compounds are avirulent in many pathogens (47)(48)(49). In contrast, amino acids appear abundant, since many (but not all) auxotrophic mutants retain full virulence (4,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that the catabolic pathways for a variety of nonsugar compounds are induced by phagocytosis and are required for fungal survival in macrophages and/or virulence in a mouse model of disseminated candidiasis (1823), suggesting that certain host niches are carbon-limited environments.…”
Section: Introductionmentioning
confidence: 96%